FEATURES OF TOUR RATING AS A TYPE OF ACTIVITY IN MODERN CRISIS CONDITIONS - KHUDAVERDIYEVA, Victoriya; OMELCHENKO, Galina; MERCHANSKYI, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of this article is to study the features of tour rating as a type of activity in the tourism market in modern crisis conditions, to assess the main problem areas of tourism in a crisis; to systematize the world and domestic experience of supporting the sphere of tourism in the current conditions; assess possible scenarios for the recovery of tourism, taking into account the measures taken by the state. Such features of tour rating require from the top management of the company significant organizational skills, skills and efficient work process in the company. Thus, the activity of a tour operator is a natural combination of work cycles for specific tours or programs.The article identifies the importance of hospitality and tourism, which is a vital source of income from tourism and foreign direct investment, as well as jobs, especially for women and youth. The beginning of hostilities on the territory of Ukraine, the closure of the borders of external and internal in February 2022, not only the income of tourism companies to zero, but also led in some cases to significant losses. The Organization for Economic Cooperation and Development (OECD) predicts an unprecedented crisis and a reduction in world tourism revenues to 45%, and if the conflict continues until September, the figure could reach 70%. As tourism is an important part of the economies of many countries, this will have a negative impact on the macroeconomic performance of countries with the most developed tourism. Many countries have taken decisive action to support the tourism sector, but this may not be enough to restore the tourism sector. One of the main goals is to support tourism companies and their employees.
Keywords: tour rating; travel agents; travel product; travel companies; travel activity